Association of psychological distress with smoking cessation, duration of abstinence from smoking, and use of non-combustible nicotine-containing products: A cross-sectional population survey in Great Britain. (March 2023) - Kock, Loren; Brown, Jamie; Cox, Sharon; McNeill, Ann; Robson, Debbie; Shahab, Lion; Tattan-Birch, Harry; Brose, Leonie S.
Highlights: Tobacco smoking cessation is associated with improvements in mental health. Never-smokers and >1 year ex-smokers had lower levels of distress than smokers. Nicotine product use among ex-smokers was associated with greater distress. Associations with nicotine product use are likely confounded by nicotine dependence. Abstract: Background: Tobacco smoking cessation is associated with improvements in mental health. This study assessed psychological distress, using the K6 non-specific screening tool ((items cover feelings of nervousness, hopelessness, restlessness, depression, 'everything an effort' and worthlessness), by smoking status, time since quit, and use of a non-combustible nicotine product. Methods: Monthly repeat cross-sectional household survey of adults (18 + ) from October 2020–February 2022 in Great Britain (N = 32, 727). Using unadjusted and adjusted logistic regression (adjusted models included socio-demographic characteristics and ever diagnosis with a mental health condition), we assessed: associations between any/serious past-month psychological distress and smoking status and time since quit, whether these relationships were moderated by ever diagnosis with a mental health condition, and associations between distress and use of a nicotine product by people who formerly smoked. Results: In the unadjusted model, those who had not smoked for > 1y and who had never smoked had lower odds of any distress (OR = 0·42, 95 % CI 0·39-0·45; OR = 0·44, 0·41-0·47) compared with those who currently smoked. Moreover, the association of lower distress in those who had not smoked for > 1y and never smoked compared with those who currently smoked was more pronounced among those who had ever been diagnosed with a mental health condition (AOR = 0·58, 0·51-0·66; AOR = 0·60, 0·53-0·67) than among those who had not (AOR = 0·86, 0·76-0·98; AOR = 0·72, 0·65-0·81). In adjusted models of people who formerly smoked, current use of any nicotine product was associated with higher odds of distress compared with not using any nicotine product (AOR 1·23, 1·06-1·42). Conclusion: People who had never smoked, or had not smoked for > 1y had lower levels of distress than those who currently smoked. The lower odds of distress among people who had not smoked for > 1y was more pronounced among those with an ever (vs never) diagnosis of a mental health condition. Nicotine product use among those who formerly smoked was associated with greater distress. Due to potential residual confounding and selection bias more research is needed to determine causality.